2019
DOI: 10.3174/ajnr.a6290
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Quality of 4D-DSA Temporal Information

Abstract: BACKGROUND AND PURPOSE: Quantification of blood flow using a 4D-DSA would be useful in the diagnosis and treatment of cerebrovascular diseases. A protocol optimizing identification of density variations in the time-density curves of a 4D-DSA has not been defined. Our purpose was to determine the contrast injection protocol most likely to result in the optimal pulsatility signal strength. MATERIALS AND METHODS: Two 3D-printed patient-specific models were used and connected to a pulsatile pump and flow system, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…showed that when using a proper protocol for the injection of contrast medium, both the spatial information of 3D-DSA (geometry) and the temporal information of 4D-DSA (flow) remained highly accurate. 12 Additionally, Sandoval-Garcia et al 16 also found complete agreement in diagnostic characteristics in images from 2D-, 3D-, and 4D-DSA datasets. For endovascular treatment of aneurysms, it is critical that precise information on vessel sizes, ostium characteristics, and parent artery branch relationships be available.…”
Section: Clinical Applications Of 4d-dsamentioning
confidence: 87%
See 2 more Smart Citations
“…showed that when using a proper protocol for the injection of contrast medium, both the spatial information of 3D-DSA (geometry) and the temporal information of 4D-DSA (flow) remained highly accurate. 12 Additionally, Sandoval-Garcia et al 16 also found complete agreement in diagnostic characteristics in images from 2D-, 3D-, and 4D-DSA datasets. For endovascular treatment of aneurysms, it is critical that precise information on vessel sizes, ostium characteristics, and parent artery branch relationships be available.…”
Section: Clinical Applications Of 4d-dsamentioning
confidence: 87%
“…Without the pulsatile information from the contrast bolus mixing with nonopacified blood between systole and diastole, it would be impossible to quantify blood flow using 4D-DSA data. 11,12 Ruedinger et al 12 reported that an injection protocol of 75% contrast (iopamidol, Isovue 370; Bracco) injected at 2.5 mL/s for 8 seconds satisfies these requirements by producing strong pulsatility in the area of interest.…”
Section: D-dsa Acquisition Technique and Injection Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…2) [2]. Similarly, the teams of Ogard, and also Sandoval-Garcia used advanced angiographic exploration in AVM patients with both 4D DSA and 2D DSA [37,38,45,46]. A good agreement between the techniques was found regarding Spetzler-Martin grade and nidus size, but less for defining the venous drainage.…”
Section: Advanced Dsamentioning
confidence: 97%
“…Third, even though two projections of 2D-DSA were acquired simultaneously, it was not possible to fully compensate for the overlapping of vasculatures. A 4D-DSA technique has been developed recently, offering both three-dimensional structure and temporal cerebrovasculature information [29]. This is a solution to the problem of overlapping vessels and has the potential to achieve better performance than 2D-DSA in the application of QDSA.…”
Section: H Study Limitationsmentioning
confidence: 99%